“More In Than Out”: Switzerland’s Association With Schengen/ Dublin Cooperation - Wichmann, Nicole (My University, 2009)
Drawing on the concepts developed in the external governance literature, this paper argues that the conclusion of the Schengen Association Agreement symbolises a qualitative change in the bilateral relations between the EU and Switzerland. The argument on the qualitative change in the intensity of relations is developed by comparing the situation in Schengen-related matters before and after the conclusion of the Swiss Schengen Association Agreement. Although the regulatory boundary was not formally shifted prior to the conclusion of the Schengen Association Agreement, various forms of policy transfer led to a high degree of policy convergence. The organisational boundary was only “tentatively” shifted in the pre-Schengen era owing to the fact that Switzerland remained excluded from the key implementation networks (SIS, Dublin). The conclusion of a dynamic integration treaty in Schengen matters shifts the EU’s regulatory boundary towards Switzerland in an unprecedented manner, a process that has been accompanied by a multiplication of possibilities for organisational inclusion. The article concludes by critically reflecting on the limited exportability of this advanced form of “flexible integration”.
Keywords: Schengen • Dublin • Internal Security • External Governance • EU; Switzerland Relations